Kelentangan Dalam Ritual Merangin Pada Upacara Erau di Tenggarong Kutai Kartanegara Kalimantan Timur - Riana Kapri (Institut Seni Indonesia Yogyakarta, 2018)
Merangin is one of the ritual stages in erau ceremony. Erau is a ceremony that held once a year to celebrate anniversary Tenggarong city. In this ceremony, there some rituals that should be held, one of them is merangin, that include in pra erau stage which have purpose to open the communicate with the unseen world. Ritual merangin is held in Serapo belian and done by belian (people who can talks the spell) for three nights. Merangin in implemetation presenting kelentangan ansamble that will be played from the beginning till the end ritual. The main purpose from ritual merangin is to telling the unseen things to attend the erau ceremony and to guard Kutai Kartanegara during the ceremony. This research using descriptive method of analysis with anthropological and ethnomusicology approach. Then, the next step is collecting the data with literature review, observation, interview and documentation to ritual merangin that held on 19th till 22nd of July 2017. This research also using theory of music function by Alan P. Merriam, cultural theory by Clifford Geertz and form of music science by Karl Edmund Prier SJ to analize the data and the answering the formulation problem. The result of this research is ritual merangin that presenting kelentangan ansamble having linkages that cant be separated because the ansamble is the part of the ritual. Kelentangan in ritual merangin have some function, that is ritual function, communication media function, and physical response function. The song that played by kelentangan ansamble having pattern which is the simple one and sounded repeated to create magical atmosphere so the message in the communication can be delivered to the unseen things.